Effects of Cognitive Behavioral Couple Therapy With Integrated Mindfulness on Mindful Attention, Depressive Symptoms, and Dyadic Adjustment in Low‐Income Couples: A Pilot Randomized Clinical Trial - Ricardo S. S. Durães; Zila Elizabeth Pulache Vargas; Ana Cristina Garcia Dias; Francisco Lotufo‐Neto; Renato T. Ramos; Antonio de Pádua Serafim (Journal of Marital and Family Therapy, 2026)
ABSTRACT Psychosocial distress can exacerbate marital conflict, maladjustment, and mental health vulnerability. This pilot randomized clinical trial examined cognitive‐behavioral couple therapy (CBCT) integrated with mindfulness in low‐income Brazilian couples (per‐capita household income up to one minimum wage). Thirty‐four participants (17 heterosexual couples) were randomized (independent computer‐generated sequence) to an experimental ( n = 16) or waitlist control group ( n = 18). We assessed dyadic adjustment, mindful attention, marital social skills, and depressive symptoms (R‐DAS, MAAS, IHSC, BDI‐II) at baseline, post‐treatment, and 3‐month follow‐up. The intervention was eight 80‐min conjoint sessions plus daily home exercises. Time × group effects favored the experimental group for dyadic adjustment, mindful attention, and depressive symptoms (all p < 0.001, = 0.20–0.37), but not marital social skills ( p = 0.14). Because two outcomes differed at baseline, effects were confirmed with baseline‐ and dependence‐adjusted sensitivity analyses. These findings provide preliminary evidence that CBCT with mindfulness may benefit disadvantaged couples.